Sorafenib Plus Hepatic Arterial Infusion Chemotherapy in Advanced Hepatocellular Carcinoma: A Systematic Review and Meta-analysis - Peichun Peng,; Peichun Peng,; Bin Wen,; Ran Chen,; Xin Deng, (Turkish Journal of Gastroenterology, 2023)
This meta-analysis aimed to determine whether sorafenib combined with hepatic arterial infusion chemotherapy is beneficial for advanced hepatocellular carcinoma. We searched PubMed, Cochrane Library, and Embase to identify comparative studies evaluating sorafenib plus hepatic arterial infusion chemotherapy versus sorafenib for advanced hepatocellular carcinoma. Overall survival, progression-free survival, objective response rate, rate of progressive disease, and adverse events were evaluated. This meta-analysis included 5 randomized controlled trials (690 patients). Pooled estimates showed that compared with sorafenib, sorafenib plus hepatic arterial infusion chemotherapy was associated with higher overall survival (hazard ratio = 0.52, 95% CI: 0.28-0.95, P = .03), progressionfree survival (hazard ratio = 0.57, 95% CI: 0.33-0.98, P = .04), objective response rate (risk ratio = 3.84, 95% CI: 1.23-12.05, P = .02), as well as higher rates of neutropenia (risk ratio = 7.90, 95% CI: 3.0-20.78, P < .0001) and thrombocytopenia (risk ratio = 2.73, 95% CI: 1.70- 4.36, P < .0001), but had no significant influence for rate of progressive disease (risk ratio = 0.76, 95% CI: 0.43-1.37, P = .37). Sorafenib plus hepatic arterial infusion chemotherapy improved overall survival, progression-free survival, and objective response rate, but it had no effect on the rate of progressive disease. Combination therapy has a survival benefit for advanced hepatocellular carcinoma patients, and adverse events can be accepted. However, more large-scale randomized controlled trials are needed for further investigation.Cite this article as: Peng P, Wen B, Chen R, Deng X. Sorafenib plus hepatic arterial infusion chemotherapy in advanced hepatocellular carcinoma: A systematic review and meta-analysis. Turk J Gastroenterol. 2023;34(4):311-321.